Environmental, economical and marketing aspects of the operation of a waste-to-energy plant in the kotsiatis landfill in Cyprus - Charalambides, Alexandros G.; Christophi, Costas A.; Savva, Petros G. (My University, 2013)
Based on the current 2008/98/EC Directive, EU Member States are obliged to establish a waste management plan, waste prevention programmes by the end of 2013 and ensure that the general public will have the opportunity to participate in the elaboration of such plans and programmes. Energy recovery is one of the options laid down in the Directive as a possible solution and thus, the current study focuses on the environmental, technical, economical and marketing aspects of the operation of a modern Waste-to-Energy (WtE) plant in the Kotsiatis landfill. The present study includes the analysis of WtE plant aspects, such as the public’s opinions, marketing and promotional activities, environmental depollution, financing options and operational costs. Personal interviews were conducted in the villages around the Kotsiatis landfill, and the techno economical study was based on the available literature. Results have shown that the construction of a WtE plant in the area will improve the quality of life of the habitants, reduce the current environmental problems, and that it is economically viable without governmental subsidy. The construction of a WtE plant that will be capable of incinerating 100,000 tonnes of waste/year will result to 11 MW of reliable power, in addition to the environmental benefits. The Net Present Value of such an investment will be €2,655,730 with an Internal Rate of Return of 10.5 %. However, the general public in the Kotsiatis village is against the construction of such a plant, but this is due to the lack of trustworthy information about incineration technologies (and renewable energy in general) from the local media. On the contrary, the general public in the vicinity of the area is in favour of a WtE plant, as they acknowledge the potential benefits.
Keywords: Waste-to-Energy; Kotsiatis landfill in Cyprus; Techno-economical assessment; Public opinion